The interconnectedness of diet choice and distance running: Results of the research understanding the NutritioN of Endurance Runners (RUNNER) Study - Turner-McGrievy, G. M.; Moore, W. J.; Barr-Anderson, D. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
This study examined differences in diet, particularly vegetarian and vegan, among ultramarathon and other long distance runners. Participants who had completed a half- (HALF), full- (FULL), or ultramarathon (ULTRA) in the past 12 months were recruited to complete an online survey assessing current diet, reason for diet, and other dietary behaviors. A total of 422 participants completed the survey (n = 125 ULTRA, n = 152 FULL, n = 145 HALF). More ULTRA participants were men (63%) (vs. FULL (37%) and HALF (23%)) and ULTRA participants reported significantly more years of running (16.2 ± 13.6) than FULL (12.1 ± 11.1, p < .05) or HALF (10.6 ± 11.6, p < .05). Body mass index (self-reported height/weight) was significantly higher in HALF (24.3 ± 4.4 kg/m2) vs. FULL (23.1 ± 3.2 kg/m2, p < .05). ULTRA runners were almost twice as likely to report following a vegan/vegetarian diet than HALF and FULL marathoners combined (B = 1.94, 95% CI = 1.08, 3.48) and reported following their current diet longer (13.7 ± 15.3 years) than HALF participants (8.6 ± 12.1 years, p = .01). ULTRA participants more commonly cited environmental concerns whereas HALF and FULL participants cited weight loss or maintenance as a reason for following their current diet. There was no difference in diet quality between ULTRA and other runners but vegan and vegetarian runners had higher diet quality scores than nonvegetarian runners (p < .001). The findings point to an interconnectedness between long distance running, diet, and diet choice and can help guide nutrition, exercise, and psychology professionals who are working with distance runners.